Production strategies: the best practices of the eletrical and eletronics industry in Brazil - Gronovicz, Marco Aurélio; Gechele Cleto, Marcelo (REBRAE, 2016)
Productive systems that efficiently meet cost, time limit and quality requirements have become increasingly relevant due to the economics and technological turbulences that periodically hit the global economy. In the electrical and electronics industry, the fierce competition has demanded innovation, dynamism, and quick answers in developing new products and production management from the enterprises. This work aims to investigate the ways of action adopted by enterprises from this industry in Brazil. The methodology analyzes in details primary data obtained from interviews, direct observation, participant observation, document analysis and study of multiple cases in 5 large and medium-scale Brazilian enterprises as a validation mechanism. The data collected and later analyzed in this survey corresponds to the period from 2011 to 2015. As a research contribution, were identified some of best practices have been chosen for the definition and implementation of their production strategies. The main similarities and differences were also highlighted, compared and analyzed among the practices adopted by the investigated enterprises and cited authors.